Implementasi Strategi Dakwah Karang Taruna dalam Mengurangi Kenakalan Remaja di Desa Mario Kecamatan Libureng Kabupaten Bone - Andi Nurfatimah; Mahmuddin; Ramsiah Tasruddin (Interaction: Jurnal Sosiologi Komunikasi, 2025)
This study examines the da'wah strategy the Youth Organization (Karang Taruna) implemented to reduce juvenile delinquency in Mario Village, Libureng District, Bone Regency. Using a descriptive qualitative method with a phenomenological approach, data were collected through observation, in-depth interviews, and documentation from key informants, including Youth Organization leaders, religious figures, community leaders, and local teenagers. Findings reveal that Karang Taruna employs a sentimental da'wah strategy that focuses on emotional approaches through multiple program dimensions: (1) religious activities, including recitation, corpse bathing training, and establishing Islamic spiritual groups (Rohis); (2) educational interventions through juvenile delinquency seminars; (3) community engagement via charity activities; and (4) talent development through sports and arts programs. The research identifies three primary challenges: limited funding resources, management turnover, human resource constraints, and declining teenage enthusiasm due to technology distractions. The study demonstrates that while the sentimental da'wah approach shows promising results in reducing juvenile delinquency, its effectiveness could be enhanced through sustainable funding mechanisms, strengthened organizational capacity, and more engaging youth-centered activities that respond to contemporary interests. This research contributes to understanding religiously informed youth intervention strategies in rural contexts and provides practical recommendations for community-based approaches to juvenile delinquency.